ASSESSMENT THE CAPACITY OF WORKING MEMORY BY COMPLEX MOTOR TASK IN 10-14 YEARS OLD CHILDREN - Balázs FÜGEDI; László BALOGH; László TÓTH; József BOGNÁR (Cluj University Press, 2015)
The aim of the present study is to examine motor learning by capacity of working memory, focusing on kinesthetic, visuospatial sketchpad in nonclinical sample of school-aged children with complex motor task. Several researches are examining the capacity of working memory but there is very little study with nonclinical sample using complex motor task in test. The information obtained was intended to provide normative data before studying clinical populations. It can be declared that by quality the retrieval from the LTM is more auspicious than the retrieval form working memory even if the items are in the process of transcription/encoding. The information gathered in working memory did not find enough connections with movement patterns that were previously stored in the LTM, so the retrieval of them was slower and more imprecise. We can state that at the retrieval/reproduction of a maximum 30 seconds long complex set of movements the last items are still in working memory. In case of complex sport movements (as our exercises also were), the recall of the beginning of a set of movements the 30 seconds seemed short time for accessing/ encoding the data to LTM.